Associated syndromes and other genetic variations at a South African cleft lip and palate clinic - H.J.S. van den Berg; S.M. du Plessis; K-W. Butow; E.M. Honey (AOSIS, 2009)
A retrospective study was done of data on all patients registered at one of the largest cleft lip and palate clinics in South Africa (n = 3174). The associated syndromes and other genetic variations [(abbreviation:) ASGV] found in the population of persons suffering from facial cleft deformities (FCD) were analysed. 832 (26.2%) cleft lip and/ or palate patients presented with ASGV. Fifty-seven different types of syndromes were recorded of which the Fairbaim-Robin appearance (FRA) (or Pierre Robin sequence) 169 (5.3%), the Demarque-van der Woude syndrome 40 (1.3%), and the holoprosencephaly sequence cases 32 (1.0%) were the three most common ones. The three most common genetic variations found in the non-syndromic patients, were heart involvement 53(1.7%), club foot 42 (1.3%) and various eye problems 39 (1.2%). The main facial cleft deformity, namely the cleft lip, alveolus and palate (CLAP), was found in 26.2% of the ASGV-group. This particular cleft deformity was recorded at 39.7% in the FCD clinic. On the other hand, the hard and soft palate cleft (hPsP) group was found in 32.9% of patients who also had ASGV; in the total group of patients registered at the clinic, it accounted for only 16.6%. This means that ASGV occur less commonly in the CLAP group of patients, than in the hPsP group of patients.